Seizures in Fragile X Syndrome: Associations and Longitudinal Analysis of a Large Clinic-Based Cohort - Berry-Kravis, Elizabeth; Filipink, Robyn A.; Frye, Richard E.; Golla, Sailaja; Morris, Stephanie M.; Andrews, Howard; Choo, Tse-Hwei; Kaufmann, Walter E.; , The FORWARD Consortium; Berry-Kravis, Elizabeth; Velinov, Milen; Talboy, Amy L.; et al. (Frontiers in Pediatrics, 2021)
Fragile X syndrome (FXS), the most common inherited cause of intellectual disability, learning disability and autism spectrum disorder, is associated with an increased prevalence of certain medical conditions including seizures. The goal of this study was to better understand seizures in individuals with FXS using the Fragile X Online Registry with Accessible Research Database, a multisite observational study initiated in 2012 involving FXS clinics in the Fragile X Clinic and Research Consortium. Seizure data was available for 1607 participants, mostly male (77%) and white (74.5%). The overall prevalence of at least one seizure was 12%, with this rate being significantly higher in males than females (13.7% vs 6.2%, p<0.001). As compared to individuals with FXS without seizures, those with seizures were more likely to have autism spectrum disorder, current sleep apnea, later acquisition of expressive language, more severe intellectual disability, hyperactivity, irritability, and stereotyped movements. The mean age of seizure onset was 6.4 (SD 6.1) years of age with the great majority (>80%) having onset of seizures was before 10. For those with epilepsy, about half (52%) had seizures for more than 3 years. This group was found to have greater cognitive and language impairment, but not behavioral disruptions, compared with those with seizures for less than 3 years. Antiepileptic drugs were more often used in males (60.6%) than females (34.8%) and females more often required more than one medication. The most commonly used anticonvulsants were oxcarbazepine, valproic acid, lamotrigine and levetiracetam. The current study is the largest and first longitudinal study ever conducted to describe seizures in FXS. Overall, this study confirms previous reports of seizures in FXS and extends previous findings by further defining the cognitive and behavioral phenotype of those with epilepsy in FXS. Future studies should further investigate the natural history of seizures in FXS and the characteristics of seizures in FXS in adulthood.